تأثير التحديث المستمر لمعايير الإبلاغ المالي الدولية على النظام المحاسبي المالي - دراسة تحليلية - - جلاب, حنان (جامعة الوادي - University of Eloued, 2021)
هدفت هذه الدراسة إلى تقييم النظام المحاسبي المالي في ظل التحديث المستمر الذي تتعرض له معايير الإبلاغ المالي الدولية، ومن أجل الوصول إلى تحقيق هذا الهدف تم معالجة الإشكالية بدراسة مدى التأثر الإيجابي والسلبي للنظام المحاسبي المالي بهذا التحديث. ولقد توصلنا للعديد من النتائج تكمن في المستجدات الإيجابية الخاصة بالتحديث المستمر لمعاير الإبلاغ المالي الدولية على النظام المحاسبي المالي من تغيرات إعدادها وفق البيئة التنظيمية بإضافة بند مقترح حسب الإرشادات الغير كافية كما يؤثر هذا التحديث سلبا على النظام المحاسبي المالي المتضمن معايير الإبلاغ المالي الدولية بسبب الطبيعة القانونية له التي يصعب إدخال التعديلات عليها، وفي حالة تحديثه لمواكبة مستجدات هذه المعايير يتطلب أعباء مرتفعة. This study aimed to evaluate the financial accounting system upon continuous updating of international financial reporting standards, to achieve this goal the problem was addressed by studying the positive and negative impact of the financial accounting system with this update. The study found that the positive developments related to the continuous updating of international financial reporting standards on the financial accounting system were the changes in its preparation, according to the regulatory environment by adding a proposed item according to the instructions was not sufficient, and this update also negatively affected the financial accounting system that included international financial reporting standards due to its nature Legal issues that were difficult to amend, and in the event that it was updated to keep pace with developments, These standards, it required a heavy burden
The impact of the continuous updating of international financial reporting standards on the financial accounting system - Analytical study -
مقال
Keywords: النظام المحاسبي المالي ; التحديث المستمر ; معايير الإبلاغ المالي الدولية